Spatiotemporal utilization and feeding habits of fish community in Klang coastal mudflats, Malaysia / Lee Soon Loong - Lee , Soon Loong (2019)
The intertidal mudflats are non-vegetated coastal biotope often deemed as wastelands that should be reclaimed for coastal development. This stems from the lack of knowledge and understanding of the mudflat‘s ecology and contribution to fisheries and human welfare. This study thus investigated the mudflat‘s fish community in Klang Strait (Straits of Malacca), in particular, its species diversity, standing stocks and trophodynamics in relation to various environmental and spatio-temporal factors. Monthly and diel sampling was done using barrier net and gill nets at two mudflat sites, two monsoon seasons, and under the effect of three factors: period (wet/dry), moon phase (full/new moon) and diel (day/night). Stomach content and stable isotope analysis was conducted to elucidate the fish trophodynamics. Overall, the measured water parameters (salinity, temperature, dissolved oxygen concentration and pH) in the Klang Strait mudflats were rather homogeneous and relatively marine, but varied spatially in terms of the sediment characteristics (particle sizes, organic matter and chlorophyll a content). A total of 116 species of mainly juvenile and small-sized fish species made high-tide ingressions into the mudflats. Fish diversity and abundance varied spatially and temporally. The Bagan Sungai Buloh mudflat had higher species diversity but lower fish abundance than the Bagan Pasir mudflat. However, both sites shared 64 % common fish species mainly from the families of Ariidae, Clupeidae, Engraulidae, Mugillidae and Sciaenidae. More fishes were recorded during the northeast monsoon than southwest monsoon. Fish species composition differed between the dry and wet period of the monsoon. More species of predatory fish were observed during day time but large numbers of small fishes occurred during night time. Moon light had no effect on species composition. The mudflat fishes can be categorized into eight trophic guilds that occupied five trophic levels. Shrimp feeders formed the dominant guild supported by high abundance of shrimps from the families of Penaeidae and Sergestidae which were also fed by four other guilds. This sharing of an abundant prey (shrimp) resource may explain the many species of fish cohabiting the mudflat. A variable degree of food resource partitioning however occurred among species especially in the mixed macrobenthos feeders. Iliophages, copepod feeders and polychaete feeders exhibited specialized feeding with little food overlaps. Stable isotope analysis revealed that the mudflat‘s food web is mainly fueled by high production of the mudflat‘s microphytobenthos and phytoplankton sustained by close coupling of pelagic-benthic processes due to strong tidal mixing in the shallow water. Despite the presence of adjacent mangrove forests, the contribution of allochthonous mangrove carbon to the nutrition of mudflat fishes appears very limited. The findings of this study affirm the importance of mudflat as a feeding ground and refugia for juveniles of a diverse fish community. Most of these fishes are of commercial value or support subsistence fishing. Rational development planning and conservation of mudflats should therefore be part of any coastal zone management initiative. Meanwhile, the fisheries department should take cognizance of the vast fisheries contribution of coastal mudflats and treat them as an essential fish habitat for fisheries management.